Fear at the top: killer whale predation drives white shark absence at South Africa's largest aggregation site. Issue 2 (3rd April 2022) - Towner, AV; Watson, RGA; Kock, AA; Papastamatiou, Y; Sturup, M; Gennari, E; Baker, K; Booth, T; Dicken, M; Chivell, W; Elwen, S; Kaschke, T; et al.
Abstract : Risk-induced fear effects exerted by top predators are pervasive in terrestrial and marine systems, with lasting impacts on ecosystem structure and function. The loss of top predators can disrupt ecosystems and trigger trophic cascades, but the introduction of novel apex predators into ecosystems is not well understood. We documented the emigration of white sharks Carcharodon carcharias in response to the presence of a pair of killer whales, Orcinus orca, at a large white shark aggregation site in South Africa. Between February and June in 2017, five white shark carcasses washed up on beaches in Gansbaai, Western Cape Province, four of which had their livers removed. Sightings per unit effort (sea days) and telemetry data demonstrated that white sharks emigrated from Gansbaai following these predation events, and in response to further sightings of this pair and other killer whale pods in the vicinity. Tagging data demonstrated the immediate departure of white sharks from Gansbaai, and some sharks were subsequently moving east. Contrary to expected and well-documented patterns of white shark occurrence at this site, their sightings dropped throughout the following 2.5 years; change-point analysis on both datasets confirmed these departures coincided with killer whale presence and shark carcasses washing out. These findings suggest that white sharks respond rapidly to risk from a novel predator, and that their absence triggered the emergence of another predator, the bronze whaler Carcharhinus brachyurus . Predator–prey interactions between white sharks, other coastal sharks, and killer whales are increasing in South Africa and are expected to have pronounced impacts on the ecosystem.